A hierarchical system of covalent and dual non-covalent crosslinks promotes the toughness and self-healing properties of polymer hydrogels. Issue 24 (1st June 2022) - Lin, Yinlei; Ou, Zexian; Wang, Shuoqi; Sun, Sheng; Liu, Xiaoting; Song, Xinyan; Zhang, Haichen; Hu, Huawen; Li, Guangji
Abstract : A viable and straightforward approach based on a hierarchical system of triple crosslinks (constructed by covalent and dual non-covalent interactions) is reported for constructing a highly tough and rapid self-healing hydrogel. Abstract : While it is challenging to simultaneously achieve both high mechanical performance and self-healing ability within one polymer hydrogel network, we, herein, synthesized a novel class of hydrogels based on a combination of chemical and dual non-covalent crosslinks via micellar polymerization of 3-isocyanatomethyl-3, 5, 5-trimethylcyclohexyl isocyanate, end-capped by 2-hydroxyethyl methacrylate (IPDI-HEMA), with acrylamide (AM). The prepared hydrogels were demonstrated to possess a tensile elongation at a break of at least 1900%, a fracture energy of 138.4 kJ m −3, and remarkable self-healing behaviors ( e.g., a strong self-healing ability achieved at ambient temperature without the need for any stimulus or healing agent). The multiple crosslinks developed in this study for one polymer hydrogel network are significant steps to construct the desired functional hydrogels with excellent self-healing and mechanical properties.